2022
DOI: 10.3390/ijerph19127456
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of Minimally Invasive Non-Surgical Periodontal Therapy as an Alternative of Conventional Non-Surgical Periodontal Therapy—A Pilot Study

Abstract: Minimally invasive procedures were introduced in periodontics, which could enhance clinical outcomes and reduce post-operative discomfort. However, minimally invasive non-surgical periodontal therapy (MINST) as an alternative modality of conventional non-surgical root surface debridement has not been clearly evaluated by randomized controlled clinical trial. The present study aimed to investigate clinical outcomes and patients’ comfort feedback of MINST compared to conventional non-surgical periodontal therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…While patients in the TSG reported higher pain and discomfort scores, it is important to note that these scores remained within a tolerable range. [ 6 ] The satisfaction scores were generally high in both groups, indicating that patients in both the TSG and NSTG were content with their treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While patients in the TSG reported higher pain and discomfort scores, it is important to note that these scores remained within a tolerable range. [ 6 ] The satisfaction scores were generally high in both groups, indicating that patients in both the TSG and NSTG were content with their treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal ap surgery typically requires greater extension and/or a longer average duration of the procedure, thereby potentially exacerbating anxiety and stress among patients, and consequently leading to heightened levels of discomfort and postoperative pain [23,24]. Multiple studies have consistently demonstrated that esthetic crown lengthening is a safe and minimally morbid procedure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, gingival recessions are a factor to be considered as they are inevitable after periodontal treatment due to post-treatment swelling and tissue contraction: this may be due in part to limited vision and inadequate access, which would compromise the stability of the gingival tissue and affect the healing process [16]. This result does not show a significant difference between manual and ultrasonic treatment [9]; therefore, the second aim of this review is to show whether additional therapies, such as laser, ozone and glycine and/or erythritol therapies, can provide better clinical results in terms of periodontal indices (secondary outcome).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the combination of instruments is the most effective treatment to avoid an overtreatment: several studies have shown that an excessive use of manual instruments is not very effective in the treatment of moderate and/or severe pockets and that the width of the blade does not allow an excellent access in the forks of multi-radicular teeth [9].…”
Section: Introductionmentioning
confidence: 99%